Aid, fiscal policy and macroeconomy of Uganda: a cointegrated vector autoregressive (CVAR) approach - Bwire, Thomas (2012)
While confronting the question of aid effectiveness, an important issue (but often ignored) in the context of a developing country like Uganda is which GDP measure would be most reliable as this is crucial for measuring the macroeconomic impact of aid. The most commonly used GDP measure in the aid-growth literature is typically from World Development Indicators (WDI) or Penn World Tables (PWT) (being considered the most reliable or the easiest to obtain). However, disparities in GDP from alternative sources are common and in practice one has different estimates of the level, change and growth of GDP for the same country over the same period. This is of a particular concern especially in developing countries (without exception) where the informal and subsistence sectors are a large share of the economy (Jerven, 2010) and where not all transactions in the formal sector are recorded (MacGaffey, 1991), and the quality of data is still very poor and measurement perceptions of macroeconomic aggregates are varied and weak (Mukherjee, White and Wuyts, 1998). Because the source chosen for GDP may affect inferences on growth and economic performance for African countries, the thesis entry point was an analysis of alternative sources of GDP, and aimed to construct a consistent GDP series for Uganda. The extent of discrepancy in GDP estimates was investigated, and the year on year percentage GDP growth rates, including percentage and average growth rate discrepancies were derived, with a particular focus on sub-periods when GDP from alternative sources diverge most.